Effect of balloon pulmonary angioplasty on cardio-ankle vascular index and biventricular remodeling in patients with chronic thromboembolic pulmonary hypertension - Sato, Shuji; Ito, Takuro; Tabata, Tsuyoshi; Ogawa, Akihiro; Saiki, Atsuhito; Shimizu, Kazuhiro (Frontiers in Cardiovascular Medicine, 2023)
Background Chronic thromboembolic pulmonary hypertension (CTEPH) is caused by organized pulmonary thrombi, and pulmonary endarterectomy is the only curative treatment. Since balloon pulmonary angioplasty (BPA) has become an established therapeutic option for inoperable CTEPH, prognosis has improved. Recent reports suggest that arterial stiffness evaluated using the cardio-ankle vascular index (CAVI) may play an important role in the cardio-vascular interaction in CTEPH; however, the details remain unclear. This study aimed to clarify the role of CAVI in CTEPH through hemodynamic changes and ventricular remodeling after BPA. Methods and results A total of 23 patients with CTEPH who had undergone BPA were enrolled in this study. The mean pulmonary artery pressure (mPAP) and CAVI significantly decreased after BPA [mPAP, 34 (26–45) mmHg to 20 (19–24) mmHg, p < 0.0001; CAVI, 9.4 (8.0–10.3) to 8.3 (7.5–9.6), p = 0.004]. The echocardiographic right ventricle was significantly decreased, and the left ventricular volume was significantly increased after BPA, indicating significant biventricular remodeling after BPA. Changes in CAVI (ΔCAVI) significantly correlated with changes in mPAP (r = 0.45, p = 0.03). Additionally, ΔCAVI was significantly correlated with changes in both right ventricular area and left ventricular volume. Conclusions Arterial stiffness, evaluated using the CAVI, improved after BPA. Changes in CAVI were significantly correlated with changes in pulmonary arterial pressure and biventricular remodeling. CAVI may play an important role in cardiovascular interactions in patients with CTEPH.